Noeng Muhadjir’s Islamic Educational Philosophy and Its Paradigmatic Impact: A Case Study from Universitas Ahmad Dahlan, Indonesia - Azaki Khoirudin; Muh Saeful Effendi; Mhd Lailan Arqam; Hendra Darmawan; Hasnan Bachtiar; Muhammad Isa Anshori (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to examine Noeng Muhadjir’s perspective on constructing Islamic educational philosophy and its implications for developing scientific paradigms at Universitas Ahmad Dahlan (UAD). His ideas remain highly relevant amid the persistent dichotomy in Islamic education, which is still dominated by textual-theological reasoning and lacks empirical-rational contextualization. Design/methods/approach – This study applies an abductive approach combining library (deductive) and field (inductive) research. Data from Noeng Muhadjir’s works and interviews with UAD leaders are analyzed philosophically to explore how his educational philosophy shapes UAD’s scientific paradigm, as reflected in the Science Unification guideline. Findings – Noeng Muhadjir’s Islamic educational philosophy, inspired by Ibn Rushd’s Peripatetic tradition, is based on monism, metaphysical realism, and theocratic humanistic ethics. He integrates empirical-rational (‘aqliyah) and divine-revelatory (naqliyah) reasoning to develop theocratic humanistic science and technology. At UAD, this thought underpins the unification of general and religious sciences grounded in Islamic and Muhammadiyah values (AIK) to advance science, humanity, and universal values. Research implications/limitations – This research advances the development of an Islamic educational philosophy that is empirical-rational in method yet spiritual in orientation. Based on Islamic Peripatetic principles, it positions Islamic education as integrating both religious and general sciences through empirical and experimental approaches. This perspective ultimately eliminates the dichotomy between wājib ‘ain (religious knowledge) and wājib kifāyah (general knowledge), viewing both as equally vital elements of a unified Islamic epistemology. Originality/value – Until now, much research and development in Islamic educational philosophy has tended to rely on Western philosophical frameworks rather than being grounded in authentic Islamic philosophical thought. In response, Noeng Muhadjir proposes Islamic Peripatetic philosophy as a genuine form of Islamic philosophy that serves as the foundation for developing an Islamic educational philosophy rooted in empirical and rational reasoning.